Impact of induction chemotherapy and socioeconomics on sinonasal undifferentiated carcinoma survival. Issue 5 (27th February 2020) - Lehrich, Brandon M.; Goshtasbi, Khodayar; Abiri, Arash; Yasaka, Tyler; Sahyouni, Ronald; Papagiannopoulos, Peter; Tajudeen, Bobby A.; Kuan, Edward C.
Abstract : Background: Sinonasal undifferentiated carcinoma (SNUC) is an uncommon malignancy of the nasal cavity and accessory sinuses with limited available studies evaluating role of induction chemotherapy (IC), demographics, and socioeconomic factors on overall survival (OS). Methods: The 2004‐2015 National Cancer Database was queried for patients with histologically confirmed SNUC. IC was defined as chemotherapy administered 6 months to 2 weeks before surgery or ≥45 days before radiotherapy. Results: Of 440 identified patients, 70 (16%) underwent treatments involving IC. This consisted of 52 (12%), 15 (3%), and 3 (1%) patients receiving IC before definitive radiation therapy, surgery and adjuvant radiotherapy, or surgery only, respectively. On univariate analysis, IC ( p = 0.34) did not affect OS, whereas having government insurance (hazard ratio [HR], 1.79; 95% confidence interval [CI], 1.37‐2.34; p < 0.001) and living in regions with ≥13% of the population without a high school diploma (HR, 1.38; 95% CI, 1.06‐1.79; p = 0.02) were associated with worse OS. On log‐rank test, patients with advanced stage had similar OS regardless of whether or not they received IC ( p = 0.96). Patients who received IC lived closer to their treatment site ( p = 0.02) and had worse overall health, with more comorbidities ( p = 0.02). The timing of IC before definitive surgery or radiation did not affect OS ( p = 0.69). Conclusion: In this SNUC population‐based analysis, IC did not appear to provide additional OS benefit regardless of disease stage or timing before definitive treatment. Distance to treatment and level of comorbidities may be associated with receiving IC, whereas type of insurance and residence education level may impact SNUC OS, regardless of treatment.